Retroperitoneal schwannoma during pregnancy: A case report and practice-based overview - Stefano Fruci; Anna Fagotti; Silvia Salvi; Pierpaolo Mattogno; Quintino Giorgio D'Alessandris; Federica Totaro Aprile; Antonia Carla Testa; Antonio Lanzone; Liverana Lauretti (Elsevier, 2024)
The retroperitoneum is the rarest site for Schwannomas, tumors that originate from Schwann cells and usually present as benign, slowly growing masses. During pregnancy, the routine application of ultrasound for fetal assessment has led to an increased rate of detection of maternal asymptomatic masses, notably including the retroperitoneal ones. While most of these masses prove to be benign, it is imperative to consider the potential for malignancy. This report presents a rare case involving a woman diagnosed with bilateral adnexal cysts and a pre-sacral retroperitoneal mass during the first trimester of pregnancy. Surgical intervention was employed to remove ovarian tumors, and a biopsy was performed on the non-adnexal tumor to determine its nature. The histological examination revealed a bilateral borderline seromucinous tumor in the ovaries and identified a Schwannoma in the sacral mass. Despite the considerable size of the pre-sacral mass, which significantly impacted the patient's quality of life, successful measures were taken to achieve a near-term pregnancy, culminating in the delivery of a healthy baby. Subsequently the patient underwent neurosurgical treatment of the substantial pre-sacral Schwannoma. The discovery of a Schwannoma during pregnancy can evoke concerns among healthcare practitioners, touching upon potential malignancy risks, accelerated tumor growth, and impacts on fetal well-being. This paper provides a comprehensive, practice-based overview of these critical aspects.